2002
DOI: 10.1191/1352458502ms836oa
|View full text |Cite
|
Sign up to set email alerts
|

A study of therapy-related acute leukaemia after mitoxantrone therapy for multiple sclerosis

Abstract: To evaluate the incidence of therapy-related acute leukaemia (t-AL) after single-agent mitoxantrone (MITO) treatment, we reviewed medical records of patients in three studies of single-agent MITO therapy for multiple sclerosis (MS) and existing literature on MITO therapy in MS, leukaemia, and solid tumors. Of 1378 MITO recipients in the three MS studies (mean cumulative dose of 60 mg/m2 and mean follow-up of 36 months), one patient had t-AL, an observed incidence proportion of 0.07% [95% confidence interval (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(70 citation statements)
references
References 19 publications
0
66
0
4
Order By: Relevance
“…The authors found the t-AML rate was found to be relatively low (0.15%). 97 Meanwhile, in a post-marketing report for mitoxantrone-treated multiple sclerosis patients from 2003 99 Pascual et al prospectively studied the rate of AML in two Spanish cohorts, from Valencia (n=142) and from Catalonia (n=88), of mitoxantrone treated multiple sclerosis patients. The cummulative incidence and incidence density of AML for the Valencian cohort were 2.82 and 0.62% respectively; and 2.27 and 0.44% for the Catalonian cohort.…”
Section: The Association Between Multiple Sclerosis and Myeloid Leukemiamentioning
confidence: 99%
“…The authors found the t-AML rate was found to be relatively low (0.15%). 97 Meanwhile, in a post-marketing report for mitoxantrone-treated multiple sclerosis patients from 2003 99 Pascual et al prospectively studied the rate of AML in two Spanish cohorts, from Valencia (n=142) and from Catalonia (n=88), of mitoxantrone treated multiple sclerosis patients. The cummulative incidence and incidence density of AML for the Valencian cohort were 2.82 and 0.62% respectively; and 2.27 and 0.44% for the Catalonian cohort.…”
Section: The Association Between Multiple Sclerosis and Myeloid Leukemiamentioning
confidence: 99%
“…25 An early review estimated that the risk of TRAL in the MS population was 0.07% after a mean follow-up of 36 months in 1,378 patients. 26 These data were based on the MIMS study 2 (124 patients) and the aforementioned multicenter French 8 (802 patients) and single-center German 9 studies (452 patients). No TRAL was seen in the MIMS or German cohorts, but one case was seen in the French study.…”
mentioning
confidence: 99%
“…Ghalie et al 7 evaluated the incidence of therapy related acute leukemia after MX reviewing the records of 1,378 MX recipients in three MS studies (mean cumulative dose of 60 mg/m 2 and mean follow-up of 36 months) and found only one case of acute promyelocytic leukaemia (APML) detected five years after initiating MX (mean incidence proportion 0.07%). Brassat et al 6 detected only one case of trAML (FAB M5) (in a cohort of 802 French patients with MS treated with MX (incidence ≅ 0.25%).…”
Section: Discussionmentioning
confidence: 99%